Virtual Tour Grand Design Destinasi Wisata Monumen Kresek Berbasis VR - Masbahah (E-Jurnal Universitas Samudra, 2024)
Tourism development is used as one of the strategies of the Madiun Regency government in increasing regional competitiveness. One of the leading tourist destinations that will be developed by the Madiun Regency government, especially DISPARPORA, is the Kresek Monument. The Kresek Monument is one of the leading tourist destinations based on history and culture in Madiun Regency. One of DISPARPORA's efforts in developing the tourist area is by introducing the Grand Design of the Kresek Monument to investors. So that investors are more interested, the Grand Design is packaged in a Virtual Reality-based virtual tour where investors can get an immersive sensation as if they were at the Kresek Monument which will be developed. The purpose of this research is to develop a Virtual Tour Grand Design Application for the Kresek Monument Tourism Destination based on VR. The method used in the development is MDLC (Multimedia Development Life Cycle) which consists of 6 stages namely concept, design, material gathering, assembly, testing, and distribution. The grand design describes the parts of the area to be developed at the Kresek Monument in a 3D object, including the Gate area, dining area, prayer room area, garden area 1, garden area 2, plaza area, play area, parking area, and historic statue area. The VR application that has been developed is tested for functionality using black box testing, the results show that the virtual tour grand design application for the Kresek Monument Tourism Destination, Madiun Regency is functionally running according to requirements.